Abnormalities of serum-free light chain in patients with primary antibody deficiency in the absence of B lymphocyte clonality. Issue 12 (21st September 2012) - Unsworth, David Joseph; Wallage, Michael John; Sarkar, Esha; Lock, Robert John
Abstract : Aims: A review of practice to determine whether serum-free light chain (SFLC) assays are helpful in detecting underlying clonal B-cell disorders or amyloidosis in patients with primary antibody deficiency (PAD) and recurrent infection. Methods: SFLC were assayed by nephelometry (BN2 nephelometer, Siemens; FREELITE assay, Binding Site). We reviewed SFLC test results recorded in our regional laboratory over a 4-year time period; 20 adults with PAD were identified as having been tested on at least two occasions. Results: Of 20 patients, 4 with PAD had abnormal serum-free kappa/lambda (K/L) ratios but no evidence of B-cell clonality. We also found extremely low levels of kappa and or lambda (below the limits of reliable detection) in 19/20 PAD cases (mostly common variable immunodeficiency), such that in many, ratios were not calculable. Conclusions: The data suggest that the abnormal ratios are generated by an inability to produce and/or secrete SFLCs, particularly kappa FLC. In this small initial study, we seek to highlight PAD cases where a suspicious K/L ratio, typically with very low absolute quantities of SFLCs, most likely points to B-cell dysfunction, rather than to B lymphocyte clonality.